Pengembangan Video Pembelajaran Matematika Berbantuan Media Sosial Instagram sebagai Alternatif Pembelajaran - Akbar, Reza Rizki Ali; Komarudin, Komarudin (Desimal: Jurnal Matematika, 2018)
This study aims to develop and test the feasibility of instructional videos of assisted social media Instagram as an alternative learning based on the feasibility of the assessment of media experts and materials experts. This research method is 7 stages from 10 stages of Borg and Gall model which have been modified by Sugiyono covering Potency and Problem, Collecting Data, Product Design, Design Validation, Design Revision, Product Trial and Product Revision. This research produces a medium of instructional video of math-aided social media of Instagram which has been declared valid and proper to be used as media of mathematics learning by 3 material experts get average score 88,8 (Very worthy) and 3 media expert with average score 93,55 (Very Eligible) with each maximum score of eligibility is 100. So it can be concluded that the instructional media of instructional-assisted mathematics Instagram as a valid learning alternative and suitable for use as a medium of learning mathematics.